Comparison of Pregnancy Loss Proportions Between Pregnant Women with Mild and Moderate-Severe Systemic Lupus Erythematosus - Dinda Husna Azalia Soesetyo; Muhammad Adrianes Bachnas; Lilik Wijayanti; Abdurahman Laqif (Journal of Maternal and Child Health, 2024)
Background: Pregnancy in systemic lupus erythematosus (SLE) patients is considered high-risk due to potential negative impacts on both the mother and fetus, such as pregnancy loss. One of the factors influencing pregnancy loss in SLE patients is increased lupus activity and antiphospholipid syndrome (APS). This study aimed to evaluate the relationship between pregnancy loss and SLE disease activity levels. Subjects and Method: This cross-sectional study conducted at Dr. Moewardi Hospital. The population consisted of pregnant women with SLE treated at RSUD Dr. Moewardi between 2021 and 2023. A total of 81 pregnant patients with SLE selected through purposive sampling. The dependent variable was pregnancy loss. The independent variable was pregnant women with SLE. This study utilized tools and materials in the form of medical record data from the Obstetrics and Gynecology Department at Dr. Moewardi Hospital, Surakarta. Data were analyzed using bivariate analysis with SPSS software and Fisher’s exact test tests. Results: A total of 81 respondents meeting the inclusion criteria were included, consisting of 66 pregnant women with mild SLE activity and 15 pregnant women with moderate-to-severe SLE activity. There was no significant relationship between the degree of systemic lupus erythematosus activity and pregnancy loss (p =0.723). Conclusion: There is no significant association between pregnancy loss and the degree of systemic lupus erythematosus activity, whether mild or moderate-severe.